2022
DOI: 10.1101/2022.03.15.22272362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community-level characteristics of COVID-19 vaccine hesitancy in England: A nationwide cross-sectional study

Abstract: One year after the start of the COVID-19 vaccination programme in England, more than 43 million people older than 12 years old had received at least a first dose. Nevertheless, geographical differences persist, and vaccine hesitancy is still a major public health concern; understanding its determinants is crucial to managing the COVID-19 pandemic and preparing for future ones. In this cross-sectional population-based study we used cumulative data on the first dose of vaccine received by 01-01-2022 at Middle Su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…[2][3][4] Studies have shown lower vaccine uptake in areas with a higher proportion of minority ethnic groups: certain racialized populations were less vaccinated or more hesitant to receive a COVID-19 vaccine than others. [5][6][7] The ongoing inequalities faced by racialized populations have been exacerbated and amplified by the pandemic. 8 Infections, hospital admissions and deaths due to COVID-19 have disproportionately affected these populations.…”
mentioning
confidence: 99%
“…[2][3][4] Studies have shown lower vaccine uptake in areas with a higher proportion of minority ethnic groups: certain racialized populations were less vaccinated or more hesitant to receive a COVID-19 vaccine than others. [5][6][7] The ongoing inequalities faced by racialized populations have been exacerbated and amplified by the pandemic. 8 Infections, hospital admissions and deaths due to COVID-19 have disproportionately affected these populations.…”
mentioning
confidence: 99%